Issues in the Study of Osteochondrosis - Saidumarova Marguba Tulanovna (Genius Journals, 2023)
The article under discussion depicts issues in the study of osteochondrosis. The author of the article considers that the causes of changes in the intervertebral discs are not fully understood. Treatment of osteochondrosis and its complications is carried out using conservative methods aimed at eliminating pain syndrome, spinal root dysfunction and prevention of progression of dystrophic changes in the structures of the spine. If prevention and treatment of osteochondrosis are not carried out, the disease will progress, gradually affecting the entire spine, which may eventually lead to a herniated disc, pinched nerve endings and spinal cord areas. In severe cases, the consequences of osteochondrosis can only be eliminated by surgery with a long recovery and rehabilitation period
Keywords: osteochondrosis; spondyloarthrosis; disease; dynamic nature